BRS 137: soybean cultivar for southern Brazil - Bonato, Emídio Rizzo; Bertagnolli, Paulo Fernando; Linhares, Aroldo Gallon; Costamilan, Leila Maria; Kiihl, Romeu Afonso de Souza; Almeida, Leones Alves de (Pesquisa Agropecuaria Brasileira, 2001)
The goals of the soybean breeding program for the release of a new cultivar include high yield potential and resistance to diseases in order to improve Brazilian production. The cultivar BRS 137 is a result of the soybean breeding program of Embrapa (Brazil). Prior to its release, the cultivar had shown a mean grain yield potential 2% higher than the cultivar IAS 5 in 24 environments in the State of Rio Grande do Sul, Brazil. Moreover, it is resistant to bacterial pustule (Xanthomonas axonopodis pv. glycines), soybean stem canker (Diaporthe phaseolorum f. sp. meridionalis), brown stem rot (Phialophora gregata), frogeye leaf spot (Cercospora sojina), and powdery mildew (Microsphaera diffusa). The cultivar is being indicated to be cropped in the Rio Grande do Sul state for sowing from mid October to the end of November with a maximum population of 300,000 plants/ha.